Peran Kelembagaan Mancuana Popa’Ano dalam Menjaga Kelestarian Hutan Kaombo di Kelurahan Gonda Baru Kecamatan Sorawolio Kota Baubau - Sahril Sahril; La Nalefo; Nur Isiyana Wianti (Fakultas Pertanian Universitas Halu Oleo, 2022)
This study aims to determine the social system in society in Gonda Baru Village. To find out the institutional role of